Sistem Informasi Geografis Tata Guna Lahan di Kabupaten Sleman - Dwi Utami Putra, Desak Made; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Geographical Information System (GIS) is a computer-based system that has the ability to store, manipulate, analyze and re-display natural conditions with the help of spatial data and non-passive data (attributes). GIS also supports decision making in planning and management, land use, natural resources, and others. Land use is very important as the development of land that has the potential for a type of plant to prevent damage to the plants and land used. Sleman Regency has a vast and fertile plantation area and has a wet tropical climate, which affects plant fertility. With the many things that affect the type of plant for a particular land, a system that can display spatial and nonspatial information is needed that relates to land use in Sleman Regency.